Socialization of the use of Digital Marketing Products Through Social Media in Kelurahan Dauh Puri, Denpasar - Ni Ketut Arniti; Nuning Indah Pratiwi; Kadek Linda Kusnita; Wahyu Indra Satria; I Gede Bagus Wiguna Dananjaya (Universitas Ibn Khaldun, 2026)
This program aims to improve the understanding and skills of business actors in utilizing social media as an effective marketing tool. In today's digital era, marketing strategies through social media are one of the key elements in increasing business competitiveness, especially for micro, small, and medium enterprises (MSMEs). This activity is carried out through several stages, starting from planning, socialization, implementation, to mentoring and evaluation in Kelurahan Dauh Puri, Denpasar, Bali. The results of this program show an increase in participants' insight into digital marketing strategies, optimization of promotional content, and utilization of paid advertising features to expand market reach. In addition, this program also has an impact on the growth of participants' businesses, as seen from the increase in customer interaction, the number of social media followers, and online transactions. To ensure the sustainability of its benefits, a digital marketing community was formed that allows participants to continue learning and sharing experiences, and further training is planned in collaboration with local governments and the business community. With this program, it is hoped that business actors can be better prepared to face the challenges of digital marketing and increase their competitiveness in an increasingly competitive market.